Brain activity in Cluster N and the hippocampus in non-migratory zebra finches completing a spatial orientation task using magnetic compass information - Madeleine I.R. Brodbeck; Rachel Muheim; Atticus Pinzon-Rodriguez; Scott A. MacDougall-Shackleton (PLoS ONE, 2026)
The songbird brain region called Cluster N has been implicated as important for low-light vision and/or the perception of Earth’s magnetic field for migratory orientation. This region of the visual Wulst is active in migratory songbirds under dim light conditions and an intact Cluster N is necessary for magnetic compass orientation in a nocturnally migrating songbird species. Given that magnetic field information is useful for orientation outside of a migration context, it is likely that Cluster N processes magnetic compass information more generally. Zebra finches ( Taeniopygia guttata ) can use magnetic compass cues to find food in a plus maze, even though they are not nocturnal migrants. Our objective was to determine if Cluster N is active when zebra finches use their magnetic compass to orient in a plus maze. Zebra finches were tested under three conditions: i) a static magnetic field that reliably indicated the food location, ii) a sweeping magnetic field, or iii) a vertical magnetic field. The latter two conditions did not provide any directional information. Brains were collected following the task and processed to label the immediate early gene zenk . We found elevated Zenk immunoreactivity in the forebrain region defined as Cluster N in other species and in the hippocampus. We found no differences in Zenk between the three magnetic field conditions, providing no conclusive evidence for whether Cluster N is involved in the processing of magnetic compass information. In conclusion, our results are consistent with the idea that Cluster N is not a brain area restricted to nocturnally migrating songbirds, but that it is also found in non-migratory birds carrying out a spatial orientation task, possibly involving magnetic compass cues, under dim light conditions.